2013
DOI: 10.1021/ma302276b
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Difference in Electric Potential within a Charged Macromolecule

Abstract: Aldrich) and palladium on activated carbon powder (Pd/C, 10%, Alfa Aesar) were used as received. Amino end-terminated polystyrene (PS) (M n = 120 × 10 3 g⋅mol −1 , M w /M n = 1.05) and amino end-terminated poly(N-isopropylacrylamide) (PNIPAM, M n = 7.1 × 10 3 g⋅mol −1 , M w /M n = 1.29) were purchased from Polymer Source (Quebéc, Canada). Water was purified with a Millipore system (18.2 MΩ•cm −1 ). All other chemical reagents were analytical grade and used as received without further purification. Spectral Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 41 publications
5
32
1
Order By: Relevance
“…18 Thanks to the higher molecular weight and star-like nature of the polymer the experimentally observed difference between the middle and the end was more pronounced (about 0.3 units of pH) than in our simulations. However, our present results cannot explain the relation between the local and bulk pH in the strong poly(styrene sulfonate), 17,45 where the ionization is independent of pH and the mechanism behind the local pH variation is presumably different.…”
Section: Local Ph and Bulk Phcontrasting
confidence: 75%
See 1 more Smart Citation
“…18 Thanks to the higher molecular weight and star-like nature of the polymer the experimentally observed difference between the middle and the end was more pronounced (about 0.3 units of pH) than in our simulations. However, our present results cannot explain the relation between the local and bulk pH in the strong poly(styrene sulfonate), 17,45 where the ionization is independent of pH and the mechanism behind the local pH variation is presumably different.…”
Section: Local Ph and Bulk Phcontrasting
confidence: 75%
“…However, investigation of the local pH near polyelectrolyte chain by means of computer simulations is lacking. Since the local pH in polyelectrolyte solutions has been measured in recent experiments, 17,18,45,46 it is timely to investigate it in computer simulations and to contrast the experimental and simulation results. Similarly, the role of polymer concentration has not been investigated in computer simulations, while its influence on the titration behaviour of weak polyelectrolytes is evidenced in experiments.…”
Section: Theory Of Ionization Of Weak Polyelectrolytesmentioning
confidence: 99%
“…This fact has been recognized since the early investigations. 2,7,9 The most recent experiments 51 using fluorescence techniques are opening an opportunity to measure polarizability effects on ionic equilibria in polyelectrolyte solutions. Theoretical formulations of this effect in crowded environments are hard and remain as one of the major challenges in polyelectrolyte physics.…”
Section: Charge and Size In Dilute Solutionsmentioning
confidence: 99%
“…112,113 This effect is observed, for example, in the Langevin simulations of Muthukumar and co-workers. 53 Second, it has been experimentally shown that the degree of counterion binding to a PE chain is higher in the middle of chain than near the chain ends, 114 since the middle of chain is more concentrated in PE charged groups than the ends. In addition, these results explain the stronger association of oppositely charged PEs with blockier sequences, which leads to larger coacervation windows in the studies of Sing and Perry, 7 Chan, 5,6 de Pablo, 115 and Fredrickson 9 and their co-workers.…”
Section: mentioning
confidence: 99%